A design of radiation-proof material for protecting the medical staff - Semenets, Vladimir; Stytsenko, Tetiana (Eastern-European Journal of Enterprise Technologies, 2016)
The use of sophisticated medical equipment that operates at microwave frequencies draws attention to the methods and means of protecting the medical staff from exposure to occupational hazards, such as electromagnetic super-high frequency (SHF) radiation. The article considers improving the properties of expanded polystyrene (EPS)-based absorbent materials with graphite additives and emphasizes the ratio “an effective protection – a cheaper production.” The test material was of two types: with a matching layer and without it. The absorbent material with a matching layer has a lower reflectance than the one without it. In addition, the reflectance of material with a matching layer is almost insensitive of the angle of incidence of electromagnetic waves. The test frequency band corresponds to reflectance higher than 30 dB and the frequency of 75 GHz – to reflectance of 40 dB. The study of a graphite-using absorbent material that provides damping of electromagnetic waves in the direction of their propagation has focused on the effect of the size of graphite particles in an aquadag on its absorptive properties. An aquadag with the graphite particles’ size of 30–70 microns has the best characteristics of the selected frequency band. The improved methods of asymptotic solution of the problem of synthesizing the non-reflective layer at the normal incidence of a plane wave have extended to the general case – an arbitrary structure of the field in the direction of the fall. It is proved that the properties of the coating are determined ultimately by the spatial inhomogeneity of the electrical and physical properties of the material in the direction of propagation of electromagnetic waves. The findings are important for further research on absorbent materials with improved properties of absorption and reflectance in a broad range of angles of incidence from the lower portion of the frequency spectrum. This study and the findings thereof allow improving the properties of the materials to ensure collective and individual protection of medical personnel from exposure to high levels of radiation.